Factors Associated With Shoulder Activity Level at Time of Surgery and at 2-Year Follow-up in Patients Undergoing Shoulder Stabilization Surgery. Issue 6 (May 2022) - Brophy, Robert H.; Dunn, Warren R.; ,; Baumgarten, Keith M.; Bishop, Julie Y.; Bollier, Matthew J.; Bravman, Jonathan T.; Feeley, Brian T.; Grant, John A.; Jones, Grant L.; Kuhn, John E.; Benjamin Ma, C.; et al.
Background: Patients undergoing shoulder stabilization surgery have been shown to have elevated activity levels. Factors associated with shoulder activity in this patient population at baseline and after surgery are unknown. Hypothesis: Patient-specific variables are associated with shoulder activity level at baseline and at 2-year follow-up in a cohort of patients undergoing shoulder stabilization surgery. Study Design: Cohort study; Level of evidence, 2. Methods: Patients undergoing shoulder stabilization surgery were prospectively enrolled. As part of the data collection process, patients completed a previously validated Shoulder Activity Scale. A regression analysis was performed to assess the association of patient characteristics with baseline and 2-year follow-up shoulder activity levels. Results: A total of 764 (n = 612 men, n = 152 women) out of 957 patients (80%) undergoing shoulder stabilization surgery with a median age of 25 years had baseline and 2-year follow-up data and were included in the current analysis. The baseline shoulder activity level was associated with race ( P < .0001) and preoperative duration of instability ( P < .0001). At 2 years, 52% of the cohort had returned to the same or higher activity level after surgery. Predictors of higher shoulder activity level at 2-year follow-up included higher baseline activity level ( P < .0001), male sex ( P < .0001), younger age ( P = .004), higher body mass index (BMI) ( P = .03), more dislocations ( P = .03), nonsmokers ( P = .04), and race ( P = .04). Conclusion: A longer duration of preoperative symptoms was associated with a lower baseline activity in this cohort. High baseline preoperative shoulder activity, younger age, male sex, higher BMI, number of dislocations, and nonsmoking status predicted higher shoulder activity 2 years after shoulder stabilization surgery. Registration: NCT02075775 (ClinicalTrials.gov identifier).